Use of reliable contraceptives and its correlates among women participating in Simulated HIV vaccine efficacy trials in key-populations in Uganda - Abaasa, Andrew (Sci Rep, 2019)
To prevent pregnancy in trials, reliable contraceptive use is key. We investigated reliable contraceptive use at baseline and six months in key-populations in Uganda, during two Simulated HIV Vaccine Efficacy trials (SiVETs). SiVETs were nested within observational cohorts of Fisherfolk (2012–2014) and Female sex workers (2014–2017). Women in the observational cohorts were screened and enrolled into the SiVET. The trial administered a licensed Hepatitis B vaccine at 0, 1 and 6 months. Contraceptive use data were recorded at baseline and follow-up clinic visits. Reliable contraceptives (injectable Depot Medroxyprogesterone Acetate (DMPA), implant, pills, and intrauterine device (IUD)) were promoted and provided to women not using a reliable method at enrolment. Overall, 367 women were enrolled. At baseline 203 (55%) reported use of reliable contraceptive. Of the 164 women not using a reliable method at enrolment, 131 (80%) started using them during follow-up bringing the overall number to 334 (91%) at the end of follow-up. Young age (≤35 years) was an independent predictor of reliable contraceptive use at both time points while other factors varied. Promotion and provision of reliable contraceptives increased the proportion using them and could help reduce the risk of pregnancy in future HIV prevention trials.